2023
DOI: 10.3390/s23104873
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a UWB Real Time Location System for Dairy Cows’ Monitoring

Abstract: In the field of precision livestock farming, many systems have been developed to identify the position of each cow of the herd individually in a specific environment. Challenges still exist in assessing the adequacy of the available systems to monitor individual animals in specific environments, and in the design of new systems. The main purpose of this research was to evaluate the performance of the SEWIO ultrawide-band (UWB) real time location system for the identification and localisation of cows during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Ultra-wideband Sewio Leonardo iMU tracking sensors (Noldus, Wageningen, the Netherlands) 24 were attached to each individual calf via a collar with a counterweight to help to maintain the position of the sensors. These UWB sensors served as transmitters sending out blinks to the anchors to calculate the tag position 30 . UWB sensors were able to obtain the position of the calves by using the time difference of the arrival of the RF signals, which provides the distance between the reference point and the sensor 31 .…”
Section: Methodsmentioning
confidence: 99%
“…The Ultra-wideband Sewio Leonardo iMU tracking sensors (Noldus, Wageningen, the Netherlands) 24 were attached to each individual calf via a collar with a counterweight to help to maintain the position of the sensors. These UWB sensors served as transmitters sending out blinks to the anchors to calculate the tag position 30 . UWB sensors were able to obtain the position of the calves by using the time difference of the arrival of the RF signals, which provides the distance between the reference point and the sensor 31 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, D'Urso et al (2023) designed the SEWIO ultrawide-band (UWB) real-time location system for the identification and localization of cows in barns and in laboratory conditions. It has been reported that the SEWIO UWB system was useful for locating an animal's position in the barn and for measuring time spent in a specific area in the barn [28]. However, it is necessary to verify the usability of vocalizations in identifying individual cows' in-field conditions in future studies.…”
Section: Individual Recognition Of Dairy Cowsmentioning
confidence: 99%